THE EFFECT OF SUCCESSOR KNOWLEDGE AND SUCCESSOR WILLINGNESS ON SUSTAINABLE INNOVATION FOR MMSMES IN SURABAYA - Yohana F. Cahya Palupi Meilani (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The purpose of this study was to determine the effect of successor knowledge on sustainable innovation and successor willingness to sustainable innovation. The method used in this study is a quantitative method, collecting data with a questionnaire given online. The data collection technique used non-probability sampling technique,  with convinience sampling. The respondent is the successor of a small-scale family business and has been established for more than 2 years in the Surabaya area. The number of samples of questionnaire data collection was given to 160 respondents. Statistical data analysis is Structural Equation Modeling with partial least squares. The results of this study indicate that successor knowledge has a positive effect on sustainable innovation, successor willingness has a positive effect on sustainable innovation, successor relationships (knowledge and willingness)  have a positive effect on sustainable innovation with moderated by the family business leaders approval (founder or senior). The research contribution gives family business managers in small-scale to provide an introduction for their successors by teaching them about the operation of family businesses that make them able to have sustainable innovations.